Entrepreneurs' creative responses to institutional challenges : insider perspectives from Sub-Saharan Africa - Eijdenberg, Emiel L.; Thompson, Neil A. (Bingley, U.K. : Emerald Publishing Limited, 2020)
Entrepreneurs' creative responses to institutional challenges in sub-Saharan Africa examines institutional constraints and enablers of Tanzanian and Zambian entrepreneurs in sustainability practices. Exploring how entrepreneurs contribute to societal and environmental well-being despite the challenging institutional context in which they operate.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Entrepreneurship -- Environmental aspects; Entrepreneurship -- Tanzania; Entrepreneurship -- Zambia; Business & Economics -- Entrepreneurship; Entrepreneurship